2021
DOI: 10.1111/1475-679x.12406
|View full text |Cite
|
Sign up to set email alerts
|

Multimarket Contact and Mutual Forbearance in Audit Markets

Abstract: Competition in audit markets is an important topic but direct tests of market competition have been limited. In this paper, we examine how audit firms behave when they are confronted with competition from another firm in a wide range of industry segments in a local market. Sharing a large number of market segments can lead to mutual forbearance among audit rivals. Such mutual forbearance is likely to manifest as higher audit fees in a market because rivals are hesitant to aggressively compete in the face of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In robustness tests, they substitute the country and industry FE with firm FE, which are finer partitions of (or nested in) countries and industries. In a similar vein, Dekeyser et al [2021] use location, industry, and year FE in their main specification. To assess robustness to finer FE, they also report specifications with combinations of those FE (e.g., location-industry or location-industry-year FE).…”
Section: Generalizabilitymentioning
confidence: 99%
“…In robustness tests, they substitute the country and industry FE with firm FE, which are finer partitions of (or nested in) countries and industries. In a similar vein, Dekeyser et al [2021] use location, industry, and year FE in their main specification. To assess robustness to finer FE, they also report specifications with combinations of those FE (e.g., location-industry or location-industry-year FE).…”
Section: Generalizabilitymentioning
confidence: 99%
“…However, this argument assumes a price competitive market. Audit research examining different “types” of auditors has validated the assumption that the audit market is a quality‐differentiated market wherein each engagement‐auditor pair has a unique production function leading to cost and quality differentiation that is often positively associated with price (Francis [2004], Francis [2011], Dekeyser, Gaeremynck, Knechel, Willekens [2021], Francis, Golshan, and Hallman [2022]). As such, competitors may find it difficult to bid away the specialization price premium.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%
“…Ettredge et al (2020) derived the Office-Client Balance in a metropolitan area as a proxy variable for audit market competition and found that greater metro-level competition among auditors was associated with higher audit quality. Dekeyser et al (2021) found that competing with the same audit firms across different industries within a geographic region leads to mutual forbearance among auditors and less price competition.…”
Section: Literature Review Of Audit Market Competitionmentioning
confidence: 99%